Analysis Of Employee Motivation And Discipline At PT. Wahana Ottomitra Multiartha Sumedang Tbk - Maulana, Frayuda Yuandika; Rahman, Erpi; Amanda, Helles (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2024)
The focus of this research is to analyze the motivation and work discipline of employees at PT Wahana Ottomitra Multiartha Sumedang Tbk. The purpose of this study is to find out how the application of work motivation and discipline at PT. Wahana Ottomitra Multiartha Sumedang Tbk, to find out the efforts to increase work motivation and discipline at PT. Wahana Ottomitra Multiartha Sumedang Tbk. The research method uses a qualitative approach. The research data uses the Miles and Huberman model, activities in data analysis which include data collection, data reduction, data presentation, and drawing conclusions. The results of the study showthat the application of work motivation has been fulfilled properly, while the application of work discipline in terms of the frequency dimension there are still several employees who are absent without explanation. Efforts to increase work motivation at PT Wahana Ottomitra Multiartha Sumedang Tbk, pay more attention to motivation in the form of rewards per division. and efforts to improve work discipline, namely paying attention to the level of absenteeism at work, thoroughness and accuracy when working